Understanding the socioeconomic characteristics of paratransit drivers and their perceptions toward electric three-wheeled rickshaws in Delhi, India. (October 2021) - Priye, Shiv; Manoj, M.; Ranjan, Rajeev
Abstract: In India, electric rickshaws (ERs) prove to be a sustainable and affordable paratransit mode for the public. The ER service is also creating employment and income opportunities for the unskilled labor force. Many Indian state governments are proposing ER services to cater to first and last-mile trips. Therefore, planners must identify the significant factors that can affect ER services' adoption and expansion. Because of this, the present study investigates the perceptions of drivers of three prominent paratransit modes toward ERs. The research also provides a better understanding of the socio-economic conditions of these paratransit drivers. The study utilizes data of 620 paratransit drivers obtained from a face-to-face survey conducted in Delhi, India. Grey relation analysis is applied to assess the three paratransit driver groups' perceptions about ERs. The data reveals that paratransit drivers belong mostly to low financial and educational backgrounds. Male drivers constitute many paratransit drivers in the city. The lack of facilities such as designated parking and fixed charging stations and fare regulation is perceived as critical ER services barriers. Similarly, the absence of separate lanes and unsafe overtaking attempts by fast-moving vehicles are the major causes of accidents involving ERs. Further, the light body of ERs and careless driving and traffic rule violations of drivers in mixed traffic conditions are the primary safety issues. The study also highlights potential policy recommendations to design an efficient electric version of the paratransit service for achieving sustainable development goals. Highlights: Male drivers constitute a significant number of paratransit drivers in India. Paratransit drivers are mostly from poor financial and educational backgrounds. Lack of facilities such as parking, fixed charging stations, and fare regulations are among the critical ER services barriers. The absence of separate lanes and unsafe overtaking attempts by fast-moving vehicles are perceived to be the major causes of accidents involving ERs. The light body of ERs, and careless driving and traffic rule violations of drivers in mixed traffic conditions are the major safety issues.